2010
DOI: 10.1111/j.1469-0691.2009.02997.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antifungal MICs for yeasts obtained using the EU-CAST method in a reference laboratory and the Etest in nine different hospital laboratories

Abstract: In routine laboratory practice, the determination of MICs of antifungals for yeasts often relies on the Etest, because of a good correlation with reference methods. However, this correlation was established through predesigned studies, rather than prospective testing.The surveillance programme of fungaemia (YEASTS programme), implemented since 2003, facilitated our comparison of the Etest and the EUCAST results, obtained on a routine basis in nine different hospitals and in a reference laboratory, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
0
36
1
1
Order By: Relevance
“…There was considerable agreement between our Etest-MICs results for antifungals including those for amphotericin B, for which clinical breakpoints have not been established yet, and the EUCAST reference method [26,27]. Similarly, Dannaoui et al, found that the level of agreement between Etest and the EUCAST reference method was 75% for amphotericin B and ranged from 71% to 87% for azoles, even when performed on a routine basis [28].…”
Section: Discussionmentioning
confidence: 85%
“…There was considerable agreement between our Etest-MICs results for antifungals including those for amphotericin B, for which clinical breakpoints have not been established yet, and the EUCAST reference method [26,27]. Similarly, Dannaoui et al, found that the level of agreement between Etest and the EUCAST reference method was 75% for amphotericin B and ranged from 71% to 87% for azoles, even when performed on a routine basis [28].…”
Section: Discussionmentioning
confidence: 85%
“…All three of the echinocandins are acknowledged as first-line agents for the treatment of invasive candidiasis, including candidemia (29). Despite the broad utilization of these agents (5,19,38,42), longitudinal surveillance studies have documented the excellent and sustained potency of all three echinocandins since the introduction of caspofungin in 2001 (6,10,11,14,15,(30)(31)(32). Although resistance to echinocandins remains uncommon among cases of invasive candidiasis, sporadic examples of clinical failure associated with elevated MICs to one or more of these agents have been reported (1,3,16,26,39).…”
mentioning
confidence: 99%
“…However, this correlation was overall lower for amphotericin B than for caspofungin, in line with data reported previously by Fleck et al (7), who found 89% and 98% EAs for amphotericin B and caspofungin, respectively. With a different study design and comparing the Etest to the EUCAST broth dilution assay, Dannaoui et al (4) previously found a 75% g mE, minor error; ME, major error; VME, very major error.…”
Section: Discussionmentioning
confidence: 99%